Peningkatan Efikasi Diri dalam Management Marah pada Pendamping ODHA Di Puskesmas Putri Ayu Kota Jambi - yuliana, yuliana; Pebrianti, Dwi Kartika; Yanti, Rahmi Dwi; Yesni, Marnila (Universitas Baiturrahim, 2025)
ODHA are people with HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome). Changes in ODHA's character are inseparable from psychological and social pressures and cause many ODHA to become depressed. Psychological and social pressures experienced by ODHA also have a negative impact on emotions. Most people know the term emotion related to anger and hatred. ODHA companions are ODHA and become an extension of nurses and even foundations in approaching ODHA. Community Service was carried out at the Putri Ayu Health Center which is a PkM partner location aimed at enabling ODHA companions to carry out independent healthy training to increase efficacy in anger management, the implementing team had previously provided spiritual mindfulness education to participants to control emotions, the next activity the team trained independent healthy skills by providing leaflets to increase self-efficacy in anger management, providing questionnaires via Google Foam, the results obtained were 12 ODHA companions, there was an increase in self-efficacy, namely in the belief in being able to overcome anger and negative feelings by 1 point, the belief in being able to overcome sadness when in difficulty 0.91 points, the belief in being able to avoid losing control when angry 1.75 points. After this activity was given to ODHA companions, it is hoped that in the future this activity will be continued to ODHA at the Kanti Sehati Foundation